Analisis Strategi Sosialisasi Pajak atas Transaksi Perdagangan melalui Sistem Elektronik (Pmse) sebagai upaya Optimalisasi Penerimaan Pajak - Achmad Barlian; Noermina Rossya; Novianita Rulandari (Jurnal Pajak Vokasi (JUPASI), 2021)
Along with the development of today's world, technological advances have affected every aspect of life. The population census by Indonesia's Central Statistics Agency (BPS) in September 2020 recorded a population of 270.20 million people, with 196.7 million internet users, or 73.7% of Indonesia's total population, until the second quarter of 2020. Internet users continue to increase, so electronic activities are inevitable. This study aims to analyze the tax campaign strategy related to transactions of Trade through the Electronic System (PMSE) as an effort to optimize tax revenues, as well as the inhibiting and driving entities in the campaign strategy. The descriptive qualitative method was used to provide information about the existing campaign strategy at the Gambir Dua Tax Office in Jakarta. Data was collected through interviews, observation, and documentation. The results show that PMSE still needs to be developed properly. Facilities and infrastructure must be adequate and up to date with the times so that taxes from PMSE transactions contribute optimally to state revenues.